Unraveling the role of Breg cells in digestive tract cancer and infectious immunity - Moreira, Helena; Dobosz, Agnieszka; Cwynar-Zając, Łucja; Nowak, Paulina; Czyżewski, Marek; Barg, Marta; Reichert, Paweł; Królikowska, Aleksandra; Barg, Ewa (Frontiers in Immunology, 2022)
Regulatory B cells (Bregs) have emerged as an immunosuppressive subset of lymphocytes that play a key role in inflammation and carcinogenesis in the gastrointestinal tract. To date, several Bregs phenotypes have been defined based on the expression of surface markers and/or the secretion of immunosuppressive cytokines such as IL-10, IL-35, and TGF-β. However, a unique Bregs marker has yet to be found. The complex mechanisms involved in the involvement of Bregs in a variety of pathological diseases and tumors associated with the gastrointestinal tract and related organs are not fully understood and are the subject of much recent research. In this review, we summarize the current state of knowledge on the function of Bregs in the immune processes related to the development and progression of the most common gastrointestinal diseases as well as parasite diseases. In addition, the relationship between the host microbiota and the function of Bregs in the context of the disturbance of mucosal immune homeostasis is also discussed.